Nodulation by Sinorhizobium meliloti originated from a mining soil alleviates Cd toxicity and increases Cd-phytoextraction in Medicago sativa L. - Ghnaya, Tahar; Mnassri, Majda; Ghabriche, Rim; Wali, Mariem; Poschenrieder, Charlotte; Lutts, Stanley; Abdelly, Chedly (Frontiers in Plant Science, 2015)
Besides their role in nitrogen supply to the host plants by the process of symbiotic N fixation, the association between legumes and Rhizobium could be interesting also for the rehabilitation of metal contaminated soils by phytoextraction. A major limitation is however the metal sensitivity of the bacterial strains. The aim of this work was to explore the usefulness of Sinorhizobium meliloti originated from a mining site in phytoextraction of Cd by Medicago sativa. Inoculated and non-inoculated plants were cultivated for 60 d on soils containing 50 or 100 mg Cd kg-1 soil. The inoculation hindered the occurrence of Cd- induced toxicity symptoms that appeared in the shoots of non-inoculated plants. This positive effect of S.meliloti colonization was accompanied by an increase in biomass production and improved nutrient acquisition as compared to non-inoculated plants. Moreover, nodulation enhanced both Cd absorption by the roots and Cd transloaction to the shoots. The amelioration of plant biomass concomitantly with the increase in Cd shoot concentration in inoculated plants led to higher potential of Cd-phytoextraction in these plants. Hence, in the presence of 50 mg Cd kg-1 in the soil, the quantities of Cd extracted in the shoots were 58 and 178 µg plant-1 in non-inoculated and inoculated plants, respectively. Thus we suggest that this association M. sativa-S. meliloti is an efficient biological system to extract Cd.